Deciphering the Role of Anions and Secondary Coordination Sphere in Tuning Anisotropy in Dy(III) Air‐Stable D5h SIMs - Gupta, Sandeep K.; Dey, Sourav; Rajeshkumar, Thayalan; Rajaraman, Gopalan; Murugavel, Ramaswamy (Chemistry : a European journal, 2022)
Precise control of the crystal field and symmetry around the paramagnetic spin centre has recently facilitated the engineering of high‐temperature single‐ion magnets (SIMs), the smallest possible units for future spin‐based devices. In the present work, we report a series of air‐stable seven coordinate Dy(III) SIMs {[L2Dy(H2O)5][X]3⋅L2⋅n(H2O), n = 0, X = Cl (1), n=1, X = Br (2), I (3)} possessing pseudo‐D5h symmetry or pentagonal bipyramidal coordination geometry with high anisotropy energy barrier (Ueff) and blocking temperature (TB). While the strong axial coordination from the sterically encumbered phosphonamide, tBuPO(NHiPr)2 (L), increases the overall anisotropy of the system, the presence of high symmetry significantly quenches quantum tunnelling of magnetization, which is the prominent deactivating factor encountered in SIMs. The energy barrier (Ueff) and the blocking temperature (TB) decrease in the order 3>2>1 with the change of anions from larger iodide to smaller strongly hydrogen‐bonded chloride in the secondary coordination sphere, albeit the local coordination geometry and the symmetry around the Dy(III) display only slight deviations. Ab initio CASSCF/RASSI‐SO/SINGLE_ANISO calculations provide deeper insights into the dynamics of magnetic relaxation in addition to the role of the secondary coordination sphere in modulating the anisotropy of the D5h systems, using diverse models. Thus, in addition to the importance of the crystal field and the symmetry to obtain high‐temperature SIMs, this study also probes the significance of the secondary coordination sphere that can be tailored to accomplish novel SIMs. Bigger the better! The change of hydrogen‐bonded halide anions in the secondary coordination sphere of a pseudo‐D5h Dy(III) single‐ion magnet shows a subtle alteration in the magnetic properties. The Ueff, TB and coercivity decrease in the order I>Br>Cl through change of anions in the secondary coordination sphere from larger iodide to smaller chloride ions.